Total quality management framework for Libyan process and manufacturing industries - Youssef, Soltan (Cranfield University, 2006)
There are many challenges facing Libyan process and manufacturing industries in today's competitive market. One of these major challenges is the ability of Libyan companies to effectively introduce quality management approaches such as Total Quality Management (TQM) that can empower their people and improve their ability to respond to international competition. The main aim of this study was to identify the drivers and barriers to the adoption of TQM in Libyan process and manufacturing industry and to develop a model through which Libyan companies could implement and maintain improved quality systems. To achieve this aim, the research approach adopted both quantitative and qualitative methods. A generic framework of the critical success factors for implementing TQM was developed from the literature and endorsed by practitioners and experts in the field. Structured questionnaires were utilized to elicit the opinions of 400 managers from the Libyan process and manufacturing industries regarding the extent of quality management initiatives implemented in these companies. Semi-structured interviews were then used to identify mangers' opinions about the topics related to TQM implementation in companies in Libya and the United Arab Emirates (UAE). The research indicates a low level of critical TQM success factors within the Libyan companies, mostly caused by a minimal awareness of TQM philosophy, methods and tools, especially among top management. It also indicates that quality initiatives and practices in Libyan companies are still in the early stages and most of the companies studied were proceeding with quality improvement programmes without a well-defined vision and objectives. Based on these results the original TQM framework was modified for use within Libyan process and manufacturing industries. The framework propagates an approach to implementation incorporating top-down deployment and bottom-up participation. It prescribes guidelines for introducing TQM in four phases and is designed to help Libyan companies get started and move step-by-step towards a TQM culture. Moving from one phase to the next depends upon the harnessing of knowledge and expertise gained during the previous phase and fulfilling each phase assessment criteria. The implementation of this model will work faster and more efficiently if there is strong commitment from the top management and employees within the Libyan companies.